Method for regulating and controlling morphology and performance of titanium dioxide photocatalyst by using oxalic acid
By using oxalic acid to regulate the morphology and performance of titanium dioxide photocatalysts, the corrosiveness and environmental pollution problems of the use of strong acids or hydrofluoric acid in the prior art are solved, and more efficient and environmentally friendly photocatalytic performance is achieved.
Patent Information
- Application Number
- CN202510093893.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, strong acids or hydrofluoric acid are often used when regulating the particle size and morphology of titanium dioxide photocatalysts to optimize their photocatalytic properties, which have problems of corrosiveness and environmental pollution.
Oxalic acid is used as a regulator to accurately control the reaction conditions and regulate the morphology and performance of the titanium dioxide photocatalyst to prepare a TiO2 photocatalyst with a specific prism-shaped morphology.
The particle size of TiO2 is significantly reduced, its dispersion and specific surface area are improved, photocatalytic efficiency is enhanced, and the method is more environmentally friendly and economical, reducing the possibility of environmental pollution.
Smart Images

Figure CN119898814A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, and in particular to a method for regulating the morphology and performance of a titanium dioxide photocatalyst by utilizing oxalic acid. Background Art
[0002] Photocatalytic technology has attracted much attention due to its high efficiency and environmental protection. 2 As one of the most commonly used photocatalytic materials, its performance is significantly affected by factors such as crystal structure, grain size and surface morphology. 2 , has become the focus of research due to its excellent photocatalytic activity. However, how to precisely control TiO 2 The particle size and morphology of organic matter to optimize its photocatalytic performance has always been an urgent problem to be solved in the scientific research field.
[0003] In traditional methods, various acids such as hydrochloric acid, sulfuric acid, and hydrofluoric acid are often introduced as inhibitors or modifiers to regulate the TiO 2 The morphology of the photocatalyst, for example, the patent document with publication number CN105776326A discloses a method for preparing titanium dioxide polyhedrons composed of hollow hexagonal prisms. This method prepares polyhedral titanium dioxide composed of hollow hexagonal prisms by adding hydrofluoric acid as an inducing agent, which has a large specific surface area and is conducive to improving the photocatalytic performance; the patent document with publication number CN104609468A discloses a method for preparing anatase titanium dioxide with a porous hexagonal prism morphology. This method prepares anatase titanium dioxide with a porous hexagonal prism morphology by adding NaF to provide F-, which has good photocatalytic performance. However, strong acids such as hydrochloric acid and sulfuric acid are corrosive to industrial applications, and fluoride ions are prone to cause environmental pollution. Therefore, it is necessary to develop a safer and more environmentally friendly TiO 2 The morphology and performance control methods of photocatalysts are particularly important. Summary of the invention
[0004] The purpose of the present invention is to provide a method for regulating the morphology and performance of titanium dioxide photocatalyst by using oxalic acid. The method uses natural and mild oxalic acid to regulate the morphology and performance of titanium dioxide photocatalyst, which is safe and environmentally friendly.
[0005] In a first aspect, the present invention provides a method for regulating the morphology and performance of a titanium dioxide photocatalyst using oxalic acid, comprising the following steps:
[0006] S1. Prepare a precursor reaction liquid: mix tetrabutyl titanate and ethanol, place in an ice water bath at 3-5°C and stir evenly, add oxalic acid solid powder, stir until the oxalic acid is dissolved, continue to keep the ice water bath, slowly add deionized water, stir and react, and after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water is 5-8:15-25:75-115, and the molar volume ratio of the oxalic acid solid powder to the ethanol is 0.8-3.2 mol / L;
[0007] S2. Preparation of precursor powder: The precursor reaction liquid is heated to the reaction temperature and kept warm. After the reaction is complete, the reaction liquid is aged. After completion, the lower suspension is removed and dried to prepare the precursor powder. The reaction temperature is 80 to 100 ° C.
[0008] S3. Calcination treatment: The precursor powder is calcined at a high temperature to prepare TiO 2 The photocatalyst powder is calcined at a temperature of 600-700°C.
[0009] Optionally, in step S1, the rate of adding deionized water is 5 to 50 drops per minute, each drop is 0.05 to 1.5 ml, the rotation speed of the stirring reaction is 300 to 1000 r / min, and the time is 0.5 to 10 hours.
[0010] Optionally, in step S2, the insulation time is 4 to 18 hours, and the aging time is 10 to 30 hours.
[0011] Optionally, in step S3, the calcination treatment time is 0.5 to 6 hours.
[0012] Optionally, in step S3, the prepared TiO 2 The photocatalyst powder is prismatic, and the TiO 2 The average length of the photocatalyst powder is 0.5 to 3 μm.
[0013] Optionally, in step S1, the molar volume ratio of the oxalic acid solid powder to the ethanol is 1.8 to 3.2 mol / L.
[0014] Optionally, in step S3, the prepared TiO 2 The photocatalyst powder has a prismatic morphology. 2 The average length of the photocatalyst powder is 0.5 to 1.2 μm.
[0015] Optionally, in step S1, the molar volume ratio of the oxalic acid solid powder to the ethanol is 2.3 to 2.7 mol / L.
[0016] Optionally, in step S3, the prepared TiO 2 The morphology of the photocatalyst powder is hexagonal. 2 The average length of the photocatalyst powder is 0.5 to 0.7 μm. 2 The surface of the photocatalyst powder forms a bulging multi-point cellular structure.
[0017] In a second aspect, the present invention provides a TiO 2 The photocatalyst powder is prepared by the above-mentioned method of using oxalic acid to regulate the morphology and performance of titanium dioxide photocatalyst.
[0018] In summary, the present invention includes at least one of the following beneficial technical effects:
[0019] 1. The present invention provides a method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid, which can significantly reduce the TiO 2 The particle size is reduced to a specific prismatic shape, and the dispersibility and specific surface area are improved, thereby providing more active sites and significantly improving the photocatalytic efficiency. Compared with the strong acid or hydrofluoric acid used in the traditional method for regulation, the present invention uses oxalic acid as a more environmentally friendly and economical regulator. This not only reduces production costs, but also reduces the possibility of environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The TiO prepared in Examples 1-4 and Comparative Examples 1-2 2 XRD pattern of the catalyst;
[0021] Figure 2 The TiO prepared in Examples 1-4 and Comparative Examples 1-2 2 SEM images of the catalysts, (a,b) S0, (c,d) S5, (e,f) S10, (g,h) S20, (i,j) S25 and (k,l) S30;
[0022] Figure 3 The TiO prepared in Examples 1-4 and Comparative Examples 1-2 2 The degradation efficiency curve of the catalyst for degrading methyl orange under simulated visible light irradiation;
[0023] Figure 4 The TiO prepared in Example 3 and Comparative Example 1 2 X-ray photoelectron spectroscopy of the catalyst. DETAILED DESCRIPTION
[0024] The present invention provides a method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid. In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] Titanium dioxide (TiO 2 The microstructure of Nano-TiO has an important influence on its photocatalytic performance. 2 by Using Oxalic Acid”, Nanomaterials, 2022, 12, 3019) reported that adding oxalic acid can effectively prevent TiO 2 The crystal form of the prepared TiO2O3 is transformed from anatase to rutile. The anatase phase has a better photocatalytic activity than the rutile phase, and significantly improves the dispersibility of the catalyst, increases the specific surface area, and reduces the recombination rate of photoinduced carriers, thereby achieving the purpose of improving the photocatalytic performance. Among them, the prepared ellipsoidal particles with a particle size of about 5 μm have the most uniform and regular morphology and the largest specific surface area, which makes their catalytic performance the best. The simulated photocatalytic degradation of methyl orange (MO) can reach a degradation rate of 98.7% within 30 minutes. However, due to the small particles, there is still a situation of partial particle agglomeration, which makes it difficult to further reduce the particle size and further improve the photocatalytic performance. On this basis, the inventor continued to study and unexpectedly found that by further precisely controlling the reaction conditions, a hexagonal TiO2O3 with a particle size of less than 3 μm can be prepared. 2 particles, and can further improve the dispersibility and specific surface area of fine particles, thereby improving the photocatalytic performance. Furthermore, hexagonal TiO 2 The particle size can be further refined to about 1μm, or even to about 0.6μm, which is reduced by nearly ten times to the nanometer level, significantly increasing the specific surface area of the particles. In addition, cellular multi-point protrusions are formed on the surface of the particles, which can provide more active sites and further improve the photocatalytic activity.
[0026] In some embodiments of the present invention, a method for regulating the morphology and performance of a titanium dioxide photocatalyst using oxalic acid is provided, comprising the following steps:
[0027] S1. Prepare a precursor reaction liquid: mix tetrabutyl titanate and ethanol, place in an ice water bath at 3-5°C and stir evenly, add oxalic acid solid powder, stir until the oxalic acid dissolves, continue to maintain the ice water bath, slowly add deionized water, stir and react, and after the reaction is complete, prepare a precursor reaction liquid, the volume ratio of the tetrabutyl titanate, ethanol and deionized water is 5-8:15-25:75-115; preferably, the volume ratio of the tetrabutyl titanate, ethanol and deionized water is 6-7:18-22:85-105; the molar volume ratio of the oxalic acid solid powder to the ethanol is 0.8-3.2 mol / L, preferably, the molar volume ratio of the oxalic acid solid powder to the ethanol is 1.8-3.2 mol / L, more preferably 2.3-3.2 mol / L; more preferably 2.3-2.7 mol / L.
[0028] S2. Preparation of precursor powder: The precursor reaction liquid is heated to the reaction temperature and kept warm. After the reaction is complete, an aging treatment is performed. After completion, the lower suspension liquid is removed and dried to prepare the precursor powder. The reaction temperature is 80 to 100 ° C. Preferably, the reaction temperature is 85 to 95 ° C.
[0029] S3. Calcination treatment: The precursor powder is calcined at a high temperature to prepare TiO 2 The photocatalyst powder is calcined at a temperature of 600 to 700°C, preferably, at a temperature of 625 to 675°C.
[0030] In some embodiments of the present invention, in step S1, the speed of adding deionized water is 5 to 50 drops per minute, each drop is 0.05 to 1.5 ml, the rotation speed of the stirring reaction is 300 to 1000 r / min, and the time is 0.5 to 10 hours; preferably, the speed of adding deionized water is 20 to 40 drops per minute, each drop is 0.8 to 1.2 ml; preferably, the rotation speed of the stirring reaction is 500 to 800 r / min, more preferably, the rotation speed of the stirring reaction is 600 to 700 r / min; preferably, the time of stirring the reaction is 2 to 8 hours, and more preferably, the time is 2 to 5h.
[0031] In some embodiments of the present invention, in step S2, the insulation time is 4 to 18 hours, preferably 6 to 12 hours, and more preferably 6 to 10 hours; the aging time is 10 to 30 hours, preferably 12 to 24 hours.
[0032] In some embodiments of the present invention, in step S3, the calcination treatment time is 0.5 to 6 hours, preferably 1 to 4 hours, and more preferably 1 to 3 hours.
[0033] In some embodiments of the present invention, in step S3, the prepared TiO2 The photocatalyst powder is prismatic, and the TiO 2 The average length of the photocatalyst powder is 0.5 to 3 μm; preferably, the TiO 2 The average length of the photocatalyst powder is 0.5 to 1.2 μm; more preferably, the TiO 2 The photocatalyst powder has a hexagonal shape; the TiO 2 The average length of the photocatalyst powder is 0.5 to 0.7 μm. 2 The surface of the photocatalyst powder forms a bulging multi-point cellular structure.
[0034] The present invention is further described in detail below in conjunction with the examples. The raw materials in the specific examples of the present invention are all commercially available unless otherwise specified.
[0035] Example 1
[0036] Example 1 provides a method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid, comprising the following steps:
[0037] S1. Prepare the precursor reaction solution: 6.8 mL of tetrabutyl titanate (C 16 H 36 O 4 Ti, 99%, CAS: 5593-70-4) was mixed with 20 mL of anhydrous ethanol (99.7%, CAS: 64-17-5), placed in an ice-water bath at 3-5°C and stirred evenly, and 1.8 g of solid oxalic acid powder (H 2 C 2 O 4 , 98%, CAS: 144-62-7), stirring until oxalic acid is dissolved, continue to keep the ice water bath, slowly add 100mL of deionized water, the drop speed is 30 drops / minute, each drop is 1ml, after completion, keep the ice water bath stirring reaction for 3h, the stirring speed is 650r / min, after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 6.8:20:100, the molar volume ratio of oxalic acid solid powder to anhydrous ethanol is 1.0mol / L, and the molar volume ratio refers to the amount of oxalic acid solid powder divided by the volume of anhydrous ethanol;
[0038] S2. Preparation of precursor powder: The precursor reaction liquid is heated to a reaction temperature of 90°C and kept in a water bath for 8 hours. After the reaction is complete, the reaction liquid is aged at room temperature for 14 hours. After the aging is completed, a layered liquid is formed. After removing the upper layer of liquid, the lower layer of suspension is taken and dried at 80°C for 5 hours to obtain a precursor solid. The precursor solid is ground into powder to obtain a precursor powder.
[0039] S3. Calcination treatment: The precursor powder is subjected to a temperature-raising calcination treatment and calcined in an air environment at 650° C. for 2 h to obtain a product powder, which is marked as S10.
[0040] Example 2
[0041] Example 2 provides a method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid, comprising the following steps:
[0042] S1. Prepare the precursor reaction solution: 6.8 mL of tetrabutyl titanate (C 16 H 36 O 4 Ti, 99%, CAS: 5593-70-4) was mixed with 20 mL of anhydrous ethanol (99.7%, CAS: 64-17-5), placed in an ice-water bath at 3-5°C and stirred evenly, and 3.6 g of oxalic acid solid powder (H 2 C 2 O 4 , 98%, CAS: 144-62-7), stirring until oxalic acid is dissolved, continue to keep the ice water bath, slowly add 100mL of deionized water, the drop speed is 30 drops / minute, each drop is 1ml, after completion, keep the ice water bath stirring reaction for 3h, the stirring speed is 650r / min, after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 6.8:20:100, the molar volume ratio of oxalic acid solid powder to anhydrous ethanol is 2.0mol / L, and the molar volume ratio refers to the amount of oxalic acid solid powder divided by the volume of anhydrous ethanol;
[0043] S2. Preparation of precursor powder: The precursor reaction liquid is heated to a reaction temperature of 90°C and kept in a water bath for 8 hours. After the reaction is complete, the reaction liquid is aged at room temperature for 14 hours. After the aging is completed, a layered liquid is formed. After removing the upper layer of liquid, the lower layer of suspension is taken and dried at 80°C for 5 hours to obtain a precursor solid. The precursor solid is ground into powder to obtain a precursor powder.
[0044] S3. Calcination treatment: The precursor powder is subjected to a temperature-raising calcination treatment and calcined in an air environment at 650° C. for 2 h to prepare a product powder, which is marked as S20.
[0045] Example 3
[0046] Example 3 provides a method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid, comprising the following steps:
[0047] S1. Prepare the precursor reaction solution: 6.8 mL of tetrabutyl titanate (C 16 H 36 O 4Ti, 99%, CAS: 5593-70-4) was mixed with 20 mL of anhydrous ethanol (99.7%, CAS: 64-17-5), placed in an ice-water bath at 3-5°C and stirred evenly, and 4.5 g of oxalic acid solid powder (H 2 C 2 O 4 , 98%, CAS: 144-62-7), stirring until oxalic acid is dissolved, continue to keep the ice water bath, slowly add 100mL of deionized water, the drop speed is 30 drops / minute, each drop is 1ml, after completion, keep the ice water bath stirring reaction for 3h, the stirring speed is 650r / min, after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 6.8:20:100, the molar volume ratio of oxalic acid solid powder to anhydrous ethanol is 2.5mol / L, and the molar volume ratio refers to the amount of oxalic acid solid powder divided by the volume of anhydrous ethanol;
[0048] S2. Preparation of precursor powder: The precursor reaction liquid is heated to a reaction temperature of 90°C and kept in a water bath for 8 hours. After the reaction is complete, the reaction liquid is aged at room temperature for 14 hours. After the aging is completed, a layered liquid is formed. After removing the upper layer of liquid, the lower layer of suspension is taken and dried at 80°C for 5 hours to obtain a precursor solid. The precursor solid is ground into powder to obtain a precursor powder.
[0049] S3. Calcination treatment: The precursor powder is subjected to a temperature-raising calcination treatment and calcined in an air environment at 650° C. for 2 h to prepare a product powder, which is marked as S25.
[0050] Example 4
[0051] Example 4 provides a method for regulating the morphology and performance of a titanium dioxide photocatalyst using oxalic acid, comprising the following steps:
[0052] S1. Prepare the precursor reaction solution: 6.8 mL of tetrabutyl titanate (C 16 H 36 O 4 Ti, 99%, CAS: 5593-70-4) was mixed with 20 mL of anhydrous ethanol (99.7%, CAS: 64-17-5), placed in an ice-water bath at 3-5°C and stirred evenly, and 5.4 g of oxalic acid solid powder (H 2 C 2 O 4, 98%, CAS: 144-62-7), stirring until oxalic acid is dissolved, continue to keep the ice water bath, slowly add 100mL of deionized water, the drop speed is 30 drops / minute, each drop is 1ml, after completion, keep the ice water bath stirring reaction for 3h, the stirring speed is 650r / min, after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 6.8:20:100, the molar volume ratio of oxalic acid solid powder to anhydrous ethanol is 3.0mol / L, and the molar volume ratio refers to the amount of oxalic acid solid powder divided by the volume of anhydrous ethanol;
[0053] S2. Preparation of precursor powder: The precursor reaction liquid is heated to a reaction temperature of 90°C and kept in a water bath for 8 hours. After the reaction is complete, the reaction liquid is aged at room temperature for 14 hours. After the aging is completed, a layered liquid is formed. After removing the upper layer of liquid, the lower layer of suspension is taken and dried at 80°C for 5 hours to obtain a precursor solid. The precursor solid is ground into powder to obtain a precursor powder.
[0054] S3. Calcination treatment: The precursor powder is subjected to a temperature-raising calcination treatment and calcined in an air environment at 650° C. for 2 h to prepare a product powder, which is marked as S30.
[0055] Comparative Example 1
[0056] Comparative Example 1: TiO 2 Photocatalyst, observe its morphology and test its photocatalytic performance:
[0057] S1. Prepare the precursor reaction solution: mix 6.8 mL of tetrabutyl titanate (99%, CAS: 5593-70-4) with 20 mL of anhydrous ethanol (99.7%, CAS: 64-17-5), place in an ice water bath at 3-5°C and stir evenly, slowly drop 100 mL of deionized water at a dropping speed of 30 drops / minute, 1 ml per drop, and after completion, keep stirring in the ice water bath for 3 hours at a stirring speed of 650 r / min. After the reaction is complete, a precursor reaction solution is prepared, wherein the volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 6.8:20:100;
[0058] S2. Preparation of precursor powder: The precursor reaction liquid is heated to a reaction temperature of 90°C and kept in a water bath for 8 hours. After the reaction is complete, the reaction liquid is aged at room temperature for 14 hours. After the aging is completed, a layered liquid is formed. After removing the upper layer of liquid, the lower layer of suspension is taken and dried at 80°C for 5 hours to obtain a precursor solid. The precursor solid is ground into powder to obtain a precursor powder.
[0059] S3. Calcination treatment: The precursor powder is subjected to a temperature-raising calcination treatment and calcined in an air environment at 650° C. for 2 h to prepare a product powder, which is marked as S0.
[0060] Comparative Example 2
[0061] Comparative Example 2 provides a method for regulating the morphology and performance of a titanium dioxide photocatalyst using oxalic acid, comprising the following steps:
[0062] S1. Prepare the precursor reaction solution: 6.8 mL of tetrabutyl titanate (C 16 H 36 O 4 Ti, 99%, CAS: 5593-70-4) was mixed with 20 mL of anhydrous ethanol (99.7%, CAS: 64-17-5), placed in an ice-water bath at 3-5°C and stirred evenly, and 0.9 g of solid oxalic acid powder (H 2 C 2 O 4 , 98%, CAS: 144-62-7), stirring until oxalic acid is dissolved, continue to keep the ice water bath, slowly add 100mL of deionized water, the drop speed is 30 drops / minute, each drop is 1ml, after completion, keep the ice water bath stirring reaction for 3h, the stirring speed is 650r / min, after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, anhydrous ethanol and deionized water is 6.8:20:100, the molar volume ratio of oxalic acid solid powder to anhydrous ethanol is 0.5mol / L, and the molar volume ratio refers to the amount of oxalic acid solid powder divided by the volume of anhydrous ethanol;
[0063] S2. Preparation of precursor powder: The precursor reaction liquid is heated to a reaction temperature of 90°C and kept in a water bath for 8 hours. After the reaction is complete, the reaction liquid is aged at room temperature for 14 hours. After the aging is completed, a layered liquid is formed. After removing the upper layer of liquid, the lower layer of suspension is taken and dried at 80°C for 5 hours to obtain a precursor solid. The precursor solid is ground into powder to obtain a precursor powder.
[0064] S3. Calcination treatment: The precursor powder is subjected to a temperature-raising calcination treatment and calcined in an air environment at 650° C. for 2 h to prepare a product powder, which is marked as S5.
[0065] Microstructure characterization:
[0066] The phase composition of the product powders of Examples 1-4 and Comparative Examples 1-2 was tested by X-ray diffractometer (XRD). The test results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the phase structures of the product powders S5, S10, S20, S25, and S30 prepared in Comparative Example 2 and Examples 1-4 are anatase TiO 2The phase structure of the product powder S0 prepared in Comparative Example 1 is rutile TiO 2 .
[0067] The microstructure of the product powders of Examples 1-4 and Comparative Examples 1-2 was tested using a scanning electron microscope (SEM). The test results are as follows: Figure 2 shown. Figure 2 (a) (b) are scanning test pictures of the product powder S0 prepared in Comparative Example 1. Figure 2 (a) (b) It was found that the TiO 2 The powder particles showed irregular block morphology, poor dispersion, small particles adsorbed on large block particles, uneven particle size distribution, and a large distribution range. The particle size measured by Nano Measurer 1.2 software was between 0.5 μm and 10 μm; Figure 2 (c) (d) are scanning test pictures of the product powder S5 prepared in Comparative Example 2. Figure 2 (c) (d) It was found that the TiO 2 Powder particles present irregular block morphology, uneven particle size distribution, small particles adsorbed on large block particles, and a wide distribution range of particle sizes, with particle sizes ranging from 0.5 microns to 10 microns; Figure 2 (e) (f) are scanning test pictures of the product powder S10 prepared in Example 1. Figure 2 (e) (f) It was found that the TiO prepared in Example 1 2 The powder particles are hexagonal, well dispersed, and evenly distributed. The average length (arithmetic mean) of the particles is 2.63um, the average width (cross-sectional length) is 1.06um, and there are a few microcracks on the particle surface. Figure 2 (g) and (h) are scanning test pictures of the product powder S20 prepared in Example 2. Figure 2 (g) (h) It was found that the TiO prepared in Example 2 2 The powder particles are hexagonal, with good dispersion and uniform particle size distribution. The average length of the particles is 0.82um, the average width is 0.42um, and the particle surface is flat. Figure 2 (i) (j) are scanning test pictures of the product powder S25 prepared in Example 3. Figure 2 (i) (j) It was found that the TiO prepared in Example 3 2 The powder particles are hexagonal, with good dispersion and uniform particle size distribution. The average length of the particles is 0.602um, the average width is 0.232um, and a bulging multi-point cellular structure is formed on the surface of the particles. Figure 2(k) (l) are scanning test pictures of the product powder S30 prepared in Example 4. Figure 2 (k)(l) It was found that the TiO prepared in Example 4 2 The powder particles are hexagonal in shape, with good dispersion and uniform particle size distribution. The average length of the particles is measured to be 1.005um, the average width is 0.54um, and there are a few microcracks on the surface.
[0068] Catalytic performance test:
[0069] 0.05 g of the product powder S10 prepared in Example 1 was added to a mixed solution containing 20 ml of 20 mg / L methyl orange (MO) solution, and the mixed solution was magnetically stirred in the dark for 30 minutes to make TiO 2 The adsorption-desorption equilibrium is established between the methyl orange molecules. After the adsorption-desorption equilibrium is reached, the light source is turned on to start the photocatalytic process. The light source uses a 300W xenon lamp as a light source to simulate sunlight, and the irradiation intensity is 100mW / cm 2 1 mL of solution was collected every 5 min, centrifuged at 8000 rpm for 10 min, the supernatant was collected, and then the absorbance of the MO supernatant was measured at a specific wavelength of λ = 470 nm using a spectrophotometer (UV-3600UV-Vis). 0 -A t ) / A 0 ×100%=(C 0 -C t ) / C 0 × 100%, calculate the degradation rate D, A 0 and C 0 represents the initial absorbance and concentration of MO, A t and C t It represents the absorbance and concentration of MO at time t. The test results are as follows Figure 3 As shown, from Figure 3 It can be seen that when the simulated light source is illuminated for 17 minutes, the degradation efficiency of S25 and S30 reaches 100.0% and 95.6% respectively. When the simulated light source is illuminated for 20 minutes, the degradation efficiency of S0, S5, S10, S20, S25 and S30 reaches 26.7%, 1.3%, 41.9%, 66.2%, 100.0% and 100.0% respectively.
[0070] Figure 4 The TiO prepared in Example 3 and Comparative Example 1 2 X-ray photoelectron spectroscopy of the catalyst, from Figure 4 It can be seen that TiO 2 The constituent elements are C, O and Ti, accompanied by the Auger electron peaks of Ti-LMM and O-KLL.
[0071] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid, characterized in that: The following steps are involved: S1. Prepare a precursor reaction liquid: mix tetrabutyl titanate and ethanol, place in an ice water bath at 3-5°C and stir evenly, add oxalic acid solid powder, stir until the oxalic acid is dissolved, continue to keep the ice water bath, slowly add deionized water, stir and react, and after the reaction is complete, prepare a precursor reaction liquid, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water is 5-8:15-25:75-115, and the molar volume ratio of the oxalic acid solid powder to the ethanol is 0.8-3.2 mol / L; S2. Preparation of precursor powder: The precursor reaction liquid is heated to the reaction temperature and kept warm. After the reaction is complete, the reaction liquid is aged. After completion, the lower suspension is removed and dried to prepare the precursor powder. The reaction temperature is 80 to 100 ° C. S3. Calcination treatment: The precursor powder is calcined at a high temperature to prepare TiO2 photocatalyst powder, and the calcination temperature is 600-700°C.
2. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to claim 1, characterized in that: In step S1, the speed of adding deionized water is 5 to 50 drops per minute, each drop is 0.05 to 1.5 ml, the rotation speed of the stirring reaction is 300 to 1000 r / min, and the time is 0.5 to 10 hours.
3. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to claim 1, characterized in that: In step S2, the insulation time is 4 to 18 hours, and the aging time is 10 to 30 hours.
4. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to claim 1, characterized in that: In step S3, the calcination treatment time is 0.5 to 6 hours.
5. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to any one of claims 1 to 4, characterized in that: In step S3, the prepared TiO2 photocatalyst powder is in a prism shape, and the average length of the TiO2 photocatalyst powder is 0.5 to 3 μm.
6. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to any one of claims 1 to 4, characterized in that: In step S1, the molar volume ratio of the oxalic acid solid powder to the ethanol is 1.8 to 3.2 mol / L.
7. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to claim 6, characterized in that: In step S3, the prepared TiO2 photocatalyst powder has a prismatic morphology, and the average length of the TiO2 photocatalyst powder is 0.5-1.2 μm.
8. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to claim 6, characterized in that: In step S1, the molar volume ratio of the oxalic acid solid powder to the ethanol is 2.3-2.7 mol / L.
9. The method for regulating the morphology and performance of titanium dioxide photocatalyst using oxalic acid according to claim 7, characterized in that: In step S3, the morphology of the prepared TiO2 photocatalyst powder is hexagonal, the average length of the TiO2 photocatalyst powder is 0.5-0.7 μm, and the surface of the TiO2 photocatalyst powder forms a bulging multi-point cellular structure.
10. A TiO2 photocatalyst powder prepared by the method for regulating the morphology and performance of a titanium dioxide photocatalyst using oxalic acid as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing anatase type titanium dioxide having porous hexagonal prism morphology, and applications of anatase type titanium dioxide having porous hexagonal prism morphology
CN104609468A
Preparation method of titanium dioxide polyhedron composed of hollow hexagonal prisms and obtained product
CN105776326A